Prevalence and Factors Associated with Abuse among Elderly in a Community of Kirtipur Municipality - Basnet, Saraswati; Rai, Aishwarya; Silwal, Suvekshya (Journal of Research and Development, 2024)
Elderly Abuse is a public Health concern. Elderly people in a community may only perceive physical abuse as an abuse and may not think other abuse as abuse to them therefore is left unrecognized and unreported. According to World Health Organization, 2021 around 1 in 6 people of age 60 years above experienced some form of abuse in community setting during past year. More research and depth study is needed regarding elderly abuse. The main objective of the study was to assess the prevalence of elderly abuse and its associated factors in community of Kirtipur municipality. A Cross-sectional study on prevalence and associated factors of abuse among elderly in a community of Kirtipur municipality was conducted. Semi-structured interview schedule was used. Data analysis was done by using SPSS version 25.0 in descriptive statistics (mean, median, standard deviation, frequency and percentage) and inferential statistics chi- square test was used to find out association between level of awareness and selected demographic variables. The findings of the study show prevalence of elderly abuse to be 11.4%. Caregiver neglect (9.5%) and psychological abuse (9.5%) were found to be most experienced by elderly. Among the socio-demographic variables the present study showed elderly abuse significantly associated (p<0.05) with elderly’s health status, elderly’s dependency level in daily living activities and involvement in income generating activities. The study concluded that elderly with poor health status, who are dependent for daily living activities and those who are not involved in income generating activities are more vulnerable to abuse. Although this study shows lower prevalence rate in elderly abuse measures need to be taken to prevent it.